Leveraging Micro-Level Building Information Modeling for Managing Sustainable Design: United Kingdom Experience. (13th June 2020) - Liu, Zhen; Wang, Yifang; Osmani, Mohamed; Demian, Peter
Abstract : Although the literature revealed the challenges and drivers to implement Building Information Modeling (BIM) in the building design industry in general, to date, there are few established methods and processes to overcome challenges of BIM adoption in building design, especially in sustainable building design for managing the project. At the present, BIM adoption in building design at micro level, that is, the level of architects, mainly focuses on barriers with little attention to method and the process of implementing BIM. Moreover, there is lack of a robust research method, that is, mixed method, to systematically investigate the process of implementing micro-level BIM in building design, which is related to the factors, such as challenges and drivers to the challenges of BIM adoption. Furthermore, several studies have looked into micro-level BIM adoption in architecture firms, but few of them focused on sustainable design. This emphasizes a need to investigate and explore micro-level BIM implementation challenges alongside its drivers in building design and present methods and processes generated from architects' perspectives to address the challenges during sustainable design for the project management, which is the aim of this paper. The research investigation was through a questionnaire that is followed by interviews with the leading architectural firms within the UK. The research reported in this paper is to present a clear view of challenges to micro-level BIM adoption and a framework/road-map to address the key challenges in managing sustainable building design projects, which are related to cultural resistance and culture change, top-down management support, current key challenges and drivers, and client and project managers' interests. The methods and processes that enhanced the framework can be instantly adopted for building design and for architectural companies including small- and medium-sized enterprises (SMEs).